Influence of Air Dissolved in Hydraulic Oil on Cavitation Erosion - Osterland, Sven; Müller, Lutz; Weber, Jürgen (International Journal of Fluid Power, 2021)
This article gives experimentally evidence that cavitation erosion in hydraulic components like valves and pumps is caused by vapour cavitation not gas or pseudo cavitation. In fact, the free air content which is released by vapour and gas cavitation reduces the erosion significantly. In order to clearly separate the different cavitation types, a test rig with a specially designed reservoir with integrated degassing capability is presented. As flow geometry a valve model with realistic dimensions and under realistic operating conditions was used, which ensures very high transferability of the results to the reality of hydraulic components in practical applications and typical operating conditions. A total of 4 five-hour long tests are performed and analysed. The quantification of the cavitation erosion is determined by the mass loss of the copper samples. The experimental results show a 4.4–5.1 times higher mass loss in tests with air-free oil compared to tests with air-saturated or oversaturated hydraulic oil. The experimental fact that air-free hydraulic oil causes significantly more cavitation erosion than normal (saturated) hydraulic oil, and its implications are discussed. The conclusion can be drawn, that further developments of hydraulic components and systems towards the use of air-free oil or increasing power densities will be disproportionately challenged by cavitation erosion.